"All I remember is the black eye": A distinctive facial feature harms eyewitness identification. Issue 6 (26th July 2020) - Jones, Alyssa R.; Carlson, Curt A.; Lockamyeir, Robert F.; Hemby, Jacob A.; Carlson, Maria A.; Wooten, Alex R.
Summary: Many crimes occur in which a perpetrator has a distinctive facial feature, such as a tattoo or black eye, but few eyewitness identification (ID) studies have involved such a feature. We conducted an experiment to determine how eyewitness ID performance is impacted by a distinctive facial feature, and how police could deal with this issue. Participants ( N = 4, 218) studied a target face with or without a black eye, and later viewed a simultaneous photo lineup either containing the target or not. For those who saw a target with a black eye, this feature was either replicated among all lineup members or was removed. The black eye harmed empirical discriminability regardless of replication or removal, which did not differ. However, participants responded more conservatively when the black eye was removed, compared to replication. Lastly, immediate confidence was consistently indicative of accuracy.